Method for producing optical glass
By adding reducing agents and defoaming agents to the raw materials of lanthanide and Si-Ti glasses and melting them in the absence of moisture, the glass coloring problem caused by platinum oxidation is solved, and high visible light transmittance and defoaming are achieved. Method for manufacturing optical glass.
Patent Information
- Application Number
- CN202411596234.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2020-01-29
- Filing Date
- 2020-03-09
- Publication Date
- 2025-02-18
AI Technical Summary
In the existing optical glass manufacturing method, oxidation of platinum leads to glass coloring, and the prior art requires adding moisture to the melting step, which increases the complexity of the manufacturing step, making it difficult to achieve high visible light transmittance and defoamability simultaneously.
Reducing agent and defoaming agent are added to the raw materials of lanthanide and Si-Ti glasses, and melting is carried out without adding moisture, inhibiting oxidation and coloring of platinum, and improving the transmittance and defoaming properties of the glass.
The tinting caused by platinum is suppressed during the melting of the glass, and the transmittance of visible light is improved, especially on the short wavelength side, and the defoaming properties of the glass are significantly improved.
Smart Images

Figure BDA0005126974690000141 
Figure BDA0005126974690000151
Abstract
Description
Technical Field
[0001] The invention relates to a method for manufacturing optical glass. Background Art
[0002] In recent years, the digitization and high-precision of equipment using optical systems have developed rapidly. In the field of various optical equipment such as digital cameras, camcorders and other photographic equipment, projectors, projection TVs and other image reproduction (projection) equipment, there is a growing demand to reduce the number of optical elements such as lenses and prisms used in the optical system and to make the overall optical system lighter and smaller.
[0003] In the manufacture of optical glass, platinum, which is often used in crucibles, etc., has a melting point of more than 1700°C, so it is suitable for melting glass. On the contrary, since it easily reacts with oxygen and deteriorates, oxidized platinum and platinum ions are easily dissolved in the glass. Platinum dissolved in the glass absorbs visible light, which causes coloring of the optical glass of the final product. In response to this, Patent Document 1 discloses a glass that reduces the reduction color and improves the defoaming property by supplying water vapor in the melting step or bubbling water vapor into the melt.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2019-19050 Summary of the invention
[0007] Technical problem to be solved by the invention
[0008] However, in the glass disclosed in Patent Document 1, water must be added in the melting step, so the glass manufacturing steps are complicated. In addition, the glass manufactured by adding a reducing agent either has a low TiO2 content or the glass obtained once must be heated again, otherwise it is difficult to obtain an optical glass with high visible light transmittance, reduced reduced color, and improved defoaming properties.
[0009] The present invention has been proposed in view of the above-mentioned technical problems, and its object is to obtain an optical glass which can suppress oxidation during the melting process of glass and coloring of glass caused by platinum dissolved in glass, has high visible light transmittance, and has improved defoaming properties by a very simple method.
[0010] Solutions to technical problems
[0011] The inventors of the present invention, in order to solve the above-mentioned technical problems, have discovered, after repeated experiments and studies, a method for manufacturing optical glass having a high transmittance of visible light by using a very simple method in which a reducing agent is included in the raw materials of lanthanum and Si-Ti glasses in an environment without adding moisture, thereby suppressing oxidation during the melting of the glass and coloring of the glass caused by platinum dissolved in the glass.
[0012] In addition, the inventors, in order to solve the above-mentioned technical problems, have conducted repeated experiments and studies and have found that by a very simple method of including a reducing agent and a defoaming agent in the raw materials of lanthanum and Si-Ti glasses without adding moisture, an optical glass with improved defoaming properties can be obtained, thereby completing the present invention.
[0013] Specifically, the present invention provides the following method.
[0014] (1) A method for manufacturing optical glass, comprising:
[0015] a step of mixing the raw materials; and
[0016] The step of melting glass without supplying water,
[0017] The raw material contains a reducing agent.
[0018] (2) A method for manufacturing optical glass, comprising:
[0019] a step of mixing the raw materials; and
[0020] The step of melting glass without supplying water,
[0021] The raw materials contain a reducing agent and a defoaming agent.
[0022] (3) The method for producing optical glass according to (1) or (2), wherein:
[0023] The optical glass contains, in terms of mass %, compared to the total mass of the glass in terms of oxide conversion composition:
[0024] 30~65% La2O3 content,
[0025] 1~25% B2O3 content,
[0026] Nb2O5 content below 15%,
[0027] SiO2 content below 15%,
[0028] TiO2 content below 25%,
[0029] Y2O3 content less than 15%.
[0030] (4) The method for producing optical glass according to (1) or (2), wherein:
[0031] The optical glass contains, in terms of mass %, compared to the total mass of the glass in terms of oxide conversion composition:
[0032] 5~75% SiO2 content,
[0033] 3-40% TiO2 content.
[0034] Effects of the Invention
[0035] The present invention has been proposed in view of the above-mentioned technical problems, and its object is to obtain an optical glass which can suppress the coloring of the glass caused by platinum that is oxidized and dissolved in the glass during the melting process of the glass, and has a high transmittance on the short wavelength side of visible light and improved defoaming properties by a very simple method. DETAILED DESCRIPTION
[0036] According to the method for manufacturing optical glass of the present invention, by making the lanthanum glass contain, by mass%, 30 to 65% of La2O3, 1 to 25% of B2O3, 15% or less of Nb2O5, 15% or less of SiO2, 25% or less of TiO2, and 15% or less of Y2O3; by making the Si-Ti glass contain, by mass%, 5 to 75% of SiO2, and 3 to 40% of TiO2, and by adding and mixing a reducing agent to the raw materials of the glass, and melting the glass without supplying water, it is possible to obtain an optical glass which can suppress the coloring of the glass caused by platinum that is oxidized and dissolved in the glass during the melting process, and has a high transmittance on the short wavelength side of visible light and improved defoaming properties.
[0037] Hereinafter, the embodiments of the optical glass and the method for manufacturing the optical glass of the present invention will be described in detail. The present invention is not limited to the following embodiments and can be appropriately changed and implemented within the scope of the purpose of the present invention. It should be noted that the description of the repeated parts may be appropriately omitted, which will not limit the purpose of the invention.
[0038] [Glass composition]
[0039] The optical glass of the present invention has two forms, namely the first glass and the second glass. The composition ranges of the components constituting the first glass and the second glass are described below. In this specification, the content of each component is expressed in mass % compared to the total mass of the oxide conversion composition unless otherwise specifically denied. Here, the "oxide conversion composition" means that, assuming that the oxides, complex salts, metal fluorides, etc. used as raw materials of the glass composition components of the present invention are all decomposed and converted into oxides during melting, the total mass of the generated oxides is recorded as 100 mass % to express the composition of each component contained in the glass.
[0040] <About the composition of the first glass>
[0041] La2O3 is an essential component in the first glass, which can increase the refractive index of the glass and improve the chemical durability of the glass. In particular, by making the content of La2O3 less than 65%, the Abbe number can be increased while improving the resistance to devitrification of the glass. Therefore, the upper limit of the content of La2O3 compared to the total mass of the glass in terms of oxide conversion composition is preferably less than 65%, more preferably less than 62%, and most preferably less than 59%. On the other hand, the lower limit of the content of La2O3 compared to the total mass of the glass in terms of oxide conversion composition is preferably more than 30%, more preferably more than 35%, and most preferably more than 40%. La2O3 can be contained in the glass using, for example, La2O3, La(NO3)3·XH2O (X is an arbitrary integer) and the like as raw materials.
[0042] B2O3 is an essential component in the first glass, and it can improve the resistance to devitrification by promoting the formation of stable glass. In particular, by making the content of B2O3 less than 25%, the reduction of the refractive index caused by the B2O3 component can be suppressed, so it is easy to obtain a high refractive index. Therefore, the upper limit of the content of the B2O3 component compared to the total mass of the glass of the oxide conversion composition is preferably less than 25%, more preferably less than 20%, and further preferably less than 15%. On the other hand, the lower limit of the content of the B2O3 component compared to the total mass of the glass of the oxide conversion composition is preferably more than 1%, more preferably more than 3%, and most preferably more than 5%. The B2O3 component can be contained in the glass using, for example, H3BO3, Na2B4O7, Na2B4O7·10H2O, BPO4, etc. as raw materials.
[0043] The Nb2O5 component is a component that can increase the refractive index and Abbe number of the glass when contained in an amount greater than 0%. On the other hand, by making the content of the Nb2O5 component 15% or less, the stability of the glass can be improved and the resistance to devitrification can be improved. Therefore, the upper limit of the content of the Nb2O5 component relative to the total mass of the glass in terms of oxide conversion composition is preferably 15% or less, more preferably 13% or less, and most preferably 11% or less. The Nb2O5 component can be contained in the glass using, for example, Nb2O5 as a raw material.
[0044] The SiO2 component is an arbitrary component in the first glass. When the content is greater than 0%, the coloring of the glass can be reduced to increase the transmittance of short-wavelength visible light, and the devitrification resistance of the glass can be improved by promoting stable glass formation. In particular, by making the content of the SiO2 component less than 15%, the reduction of the refractive index caused by the SiO2 component can be suppressed, so it is easy to obtain a high refractive index. Therefore, the upper limit of the content of the SiO2 component compared to the total mass of the glass of the oxide conversion composition is preferably less than 15%, more preferably less than 12%, and most preferably less than 9%. On the other hand, the lower limit of the content of the SiO2 component compared to the total mass of the glass of the oxide conversion composition is preferably greater than 0%, more preferably more than 1%, and most preferably more than 2%. The SiO2 component can be contained in the glass using SiO2, K2SiF6, Na2SiF6, etc. as raw materials.
[0045] TiO2 is an arbitrary component of the first glass. When the content is greater than 0%, the refractive index and Abbe number of the glass can be increased, and the chemical durability of the glass can be improved. In particular, by containing the TiO2 component, a high refractive index can be obtained, and the required Abbe number can be obtained. On the other hand, by making the content of the TiO2 component less than 25%, devitrification caused by excessive inclusion can be suppressed, and the transmittance can be suppressed. Based on the viewpoint of particularly improving the Abbe number of the glass, the lower limit of the content of the TiO2 component compared to the total mass of the glass of the oxide conversion composition is preferably greater than 0%, more preferably 3% or more, and most preferably 6% or more. On the other hand, the upper limit of the content of the TiO2 component compared to the total mass of the glass of the oxide conversion composition is preferably less than 25%, more preferably less than 20%, and most preferably less than 15%. The TiO2 component can be contained in the glass using TiO2 as a raw material, for example.
[0046] The Al2O3 component is an arbitrary component in the first glass. When the content is greater than 0%, the chemical durability of the glass can be improved, and the viscosity of the glass when it is melted can be increased. In particular, by making the content of the Al2O3 component less than 10%, the meltability of the glass can be improved, and the devitrification tendency of the glass can be reduced. Therefore, the upper limit of the content of the Al2O3 component compared to the total mass of the glass in terms of oxide conversion composition is preferably less than 10%, more preferably less than 5%, and most preferably less than 3%. The Al2O3 component can be contained in the glass using, for example, Al2O3, Al(OH)3, AlF3, etc. as raw materials.
[0047] Y2O3 is an arbitrary component of the first glass. When the content is greater than 0%, the refractive index of the glass can be increased and the Abbe number can be increased. In particular, by making the content of Y2O3 less than 15%, the devitrification resistance of the glass can be improved and the required optical coefficient can be obtained. Therefore, the upper limit of the content of Y2O3 compared to the total mass of the glass in terms of oxide conversion composition is preferably less than 15%, more preferably less than 12%, and most preferably less than 11%. On the other hand, the lower limit of the content of Y2O3 compared to the total mass of the glass in terms of oxide conversion composition is preferably greater than 0%, more preferably greater than 3%, and most preferably greater than 5%. Y2O3, for example, can be contained in the glass using Y2O3, YF3, etc. as raw materials.
[0048] The Gd2O3 component is an optional component of the first glass. When the content is greater than 0%, the refractive index of the glass can be increased and the Abbe number can be increased. In particular, by making the content of the Gd2O3 component less than 20%, the devitrification resistance of the glass can be improved and the desired optical coefficient can be obtained. The Gd2O3 component can be contained in the glass using, for example, Gd2O3, GdF3, etc. as raw materials.
[0049] The ZrO2 component is an arbitrary component in the first glass. When the content is greater than 0%, the coloring of the glass can be reduced and the transmittance to short-wavelength visible light can be increased. It can also promote stable glass formation and improve the resistance of the glass to devitrification. On the other hand, by making the content of the ZrO2 component less than 15%, the devitrification caused by the excessive content of the ZrO2 component can be reduced. Therefore, the upper limit of the content of the ZrO2 component compared to the total mass of the glass in terms of oxide conversion composition is preferably less than 15%, more preferably less than 12%, and most preferably less than 9%. On the other hand, the lower limit of the content of the ZrO2 component compared to the total mass of the glass in terms of oxide conversion composition is preferably greater than 0%, more preferably more than 1%, and most preferably more than 3%. The ZrO2 component can be contained in the glass using, for example, ZrO2, ZrF4, etc. as raw materials.
[0050] WO3 component is an arbitrary component in the first glass. When the content is greater than 0%, the refractive index and Abbe number of the glass can be increased, and the Abbe number can be increased. In particular, by making the content of WO3 component less than 15%, the devitrification resistance of the glass can be improved, and the transmittance of the glass to short-wavelength visible light can be suppressed. Therefore, the upper limit of the content of WO3 component compared to the total mass of the glass in terms of oxide conversion composition is preferably less than 15%, more preferably less than 10%, and most preferably less than 5%.
[0051] The ZnO component is an arbitrary component in the first glass. When the content is greater than 0%, the liquidus temperature of the glass can be lowered and the devitrification resistance of the glass can be improved. In particular, by making the content of the ZnO component less than 15%, a high refractive index and a low dispersion can be easily obtained. Therefore, the upper limit of the content of the ZnO component compared to the total mass of the glass in terms of oxide conversion composition is preferably less than 15%, more preferably less than 12%, and most preferably less than 9%. The ZnO component can be contained in the glass using, for example, ZnO, ZnF2, etc. as raw materials.
[0052] MgO is an arbitrary component in the first glass. When the content is greater than 0%, the liquidus temperature of the glass can be lowered, the devitrification resistance of the glass can be improved, and the transmittance of visible light is difficult to be reduced. In particular, by making the content of the MgO component less than 10%, a high refractive index and low dispersion can be easily obtained. Therefore, the upper limit of the content of the MgO component relative to the total mass of the glass in terms of oxide conversion composition is preferably less than 10%, more preferably less than 5%, and most preferably less than 3%. The MgO component can be contained in the glass using, for example, MgCO3, MgF2, etc. as raw materials.
[0053] The CaO component is an arbitrary component in the first glass. When the content is greater than 0%, the liquidus temperature of the glass can be lowered and the devitrification resistance of the glass can be improved. In particular, by making the content of the CaO component less than 20%, a high refractive index and low dispersion can be easily obtained, and the reduction of the devitrification resistance and chemical durability of the glass can be suppressed. Therefore, the content of the CaO component compared to the total mass of the glass in terms of oxide conversion composition is preferably less than 20%, more preferably less than 15%, and most preferably less than 10%. The CaO component can be contained in the glass using, for example, CaCO3, CaF2, etc. as raw materials.
[0054] The SrO component is an arbitrary component in the first glass. When the content is greater than 0%, the liquidus temperature of the glass can be lowered and the devitrification resistance of the glass can be improved. In particular, by making the content of the SrO component less than 10%, a high refractive index and low dispersion can be easily obtained, and the reduction in the devitrification resistance and chemical durability of the glass can be suppressed. Therefore, the upper limit of the content of the SrO component compared to the total mass of the glass in terms of oxide conversion composition is preferably less than 10%, more preferably less than 5%, and most preferably less than 3%. The SrO component can be contained in the glass using, for example, Sr(NO3)2, SrF2, etc. as raw materials.
[0055] BaO is an arbitrary component in the first glass. When the content is greater than 0%, the refractive index of the glass can be increased, the devitrification resistance of the glass can be increased, and the transmittance of visible light is difficult to decrease. In particular, by making the content of BaO component less than 20%, a high refractive index and low dispersion can be easily obtained, and the reduction of devitrification resistance and chemical durability can be suppressed. Therefore, the upper limit of the content of BaO component compared to the total mass of the glass in terms of oxide conversion composition is preferably less than 20%, more preferably less than 15%, and most preferably less than 10%. BaO component, for example, can be contained in the glass using BaCO3, Ba(NO3)2, BaF2, etc. as raw materials.
[0056] The Li2O component is an arbitrary component in the first glass, and when the content is greater than 0%, the melting temperature of the glass can be lowered. In particular, by making the content of the Li2O component less than 10%, a high refractive index can be easily obtained, and the stability of the glass can be improved and the occurrence of devitrification can be reduced. Therefore, the upper limit of the content of the Li2O component compared to the total mass of the glass in terms of oxide conversion composition is preferably less than 10%, more preferably less than 5%, and most preferably less than 3%. The Li2O component can be contained in the glass using, for example, Li2CO3, LiNO3, LiF, etc. as raw materials.
[0057] Na2O is an arbitrary component in the first glass, and when the content is greater than 0%, the melting temperature of the glass can be lowered. In particular, by making the content of Na2O less than 10%, a high refractive index can be easily obtained, and the stability of the glass can be improved and the occurrence of devitrification can be reduced. Therefore, the upper limit of the content of Na2O compared to the total mass of the glass in terms of oxide conversion composition is preferably less than 10%, more preferably less than 5%, and most preferably less than 3%. Na2O can be contained in the glass using, for example, Na2CO3, NaNO3, NaF, Na2SiF6, etc. as raw materials.
[0058] The K2O component is an arbitrary component in the first glass, and when the content is greater than 0%, the melting temperature of the glass can be lowered. In particular, by making the content of the K2O component less than 10%, a high refractive index can be easily obtained, and the stability of the glass can be improved and the occurrence of devitrification can be reduced. Therefore, the upper limit of the content of the K2O component compared to the total mass of the glass in terms of oxide conversion composition is preferably less than 10%, more preferably less than 5%, and further preferably less than 3%. The K2O component can be contained in the glass using, for example, K2CO3, KNO3, KF, KHF2, K2SiF6, etc. as raw materials.
[0059] The Sb2O3 component is an arbitrary component in the first glass, which can improve the transmittance of the glass to short-wavelength visible light and has a defoaming effect when melting the glass. Therefore, by making the content of the Sb2O3 component less than 0.1%, it is particularly possible to suppress coloring in the high-refractive index glass. Therefore, the content of the Sb2O3 component compared to the total mass of the glass in terms of oxide conversion composition has an upper limit of less than 0.1%, preferably less than 0.05%.
[0060] SnO2 is an arbitrary component in the first glass, and when the content is greater than 0%, it has the effect of clarifying the molten glass as a defoaming agent. In particular, by containing the SnO2 component, the above effect can be obtained, and the devitrification of the glass is less likely to occur. Therefore, the upper limit of the content of the SnO2 component compared to the total mass of the glass in terms of oxide conversion composition is preferably 2% or less, and more preferably 1% or less. The SnO2 component can be contained in the glass using SnO, SnO2, SnF2, SnF4, etc. as raw materials.
[0061] <About the composition of the second glass>
[0062] SiO2 is an essential component in the second glass. By making its content greater than 5%, the transmittance of short-wavelength visible light can be increased by reducing the coloring of the glass, and the resistance to devitrification of the glass can be improved by promoting stable glass formation. In particular, by making the content of SiO2 less than 75%, the reduction of the refractive index caused by the SiO2 component can be suppressed, so it is easy to obtain a high refractive index. Therefore, the upper limit of the content of the SiO2 component compared to the total mass of the glass of the oxide conversion composition is preferably less than 75%, more preferably less than 73%, and most preferably less than 71%. On the other hand, the lower limit of the content of the SiO2 component compared to the total mass of the glass of the oxide conversion composition is preferably more than 5%, more preferably more than 6%, and most preferably more than 7%. The SiO2 component can be contained in the glass using SiO2, K2SiF6, Na2SiF6, etc. as raw materials.
[0063] TiO2 is an essential component in the second glass. By having a content of 3% or more, the refractive index and Abbe number of the glass can be increased, and the chemical durability of the glass can be improved. In particular, by containing TiO2, a high refractive index can be obtained, and the required Abbe number can be obtained. On the other hand, by making the content of TiO2 below 40%, devitrification caused by excessive inclusion can be suppressed, and the transmittance can be suppressed. Therefore, the upper limit of the content of TiO2 compared to the total mass of the glass of the oxide conversion composition is preferably 40% or less, more preferably 38% or less, and most preferably 35% or less. On the other hand, based on the viewpoint of being able to particularly improve the Abbe number of the glass, the lower limit of the content of TiO2 compared to the total mass of the glass of the oxide conversion composition is preferably 3% or more, more preferably 4% or more, and most preferably 5% or more. TiO2, for example, can be contained in the glass using TiO2 as a raw material.
[0064] The Nb2O5 component is an arbitrary component in the second glass, and can improve the refractive index and Abbe number of the glass. In particular, by containing the Nb2O5 component, a high refractive index can be obtained, and a desired Abbe number can be obtained. On the other hand, by making the content of the Nb2O5 component less than 25%, the stability of the glass and the resistance to devitrification can be improved. Therefore, the content of the Nb2O5 component compared to the total mass of the glass in terms of oxide conversion composition is preferably 1% or more, more preferably 2% or more, and most preferably 3% or more; the upper limit is preferably 25% or less, more preferably 22% or less, and most preferably 19% or less. The Nb2O5 component can be contained in the glass using, for example, Nb2O5 as a raw material.
[0065] The B2O3 component is an arbitrary component in the second glass. When the content is greater than 0%, it can promote the formation of stable glass, thereby improving the resistance to devitrification. In particular, by making the content of the B2O3 component less than 20%, the reduction in refractive index caused by the B2O3 component can be suppressed, so it is easy to obtain a high refractive index. Therefore, the upper limit of the content of the B2O3 component compared to the total mass of the glass of the oxide conversion composition is preferably less than 20%, more preferably less than 17%, and further preferably less than 15%. The B2O3 component can be contained in the glass using, for example, H3BO3, Na2B4O7, Na2B4O7·10H2O, BPO4, etc. as raw materials.
[0066] BaO is an arbitrary component in the second glass. When the content is greater than 0%, the refractive index of the glass can be increased, the resistance to devitrification of the glass can be increased, and the transmittance to visible light is difficult to decrease. In particular, by making the content of BaO less than 25%, a high refractive index and low dispersion can be easily obtained, and the reduction in resistance to devitrification and chemical durability can be suppressed. Therefore, the upper limit of the content of BaO compared to the total mass of the glass in terms of oxide conversion composition is preferably less than 25%, more preferably less than 23%, and most preferably less than 20%. On the other hand, the lower limit of the content of BaO compared to the total mass of the glass in terms of oxide conversion composition is preferably greater than 0%, more preferably greater than 3%, even more preferably greater than 5%, and most preferably greater than 8%. BaO can be contained in the glass using, for example, BaCO3, Ba(NO3)2, BaF2, etc. as raw materials.
[0067] Na2O component is an arbitrary component in the second glass, and when the content is greater than 0%, the melting temperature of the glass can be lowered. In particular, by making the content of Na2O component less than 20%, a high refractive index can be easily obtained, and the stability of the glass can be improved and the occurrence of devitrification can be reduced. Therefore, the upper limit of the content of Na2O component compared to the total mass of the glass of oxide conversion composition is preferably less than 20%, more preferably less than 17%, and most preferably less than 14%. On the other hand, the lower limit of the content of Na2O component compared to the total mass of the glass of oxide conversion composition is preferably greater than 0%, more preferably greater than 3%, even more preferably greater than 5%, and most preferably greater than 8%. Na2O component, for example, can be contained in the glass using Na2CO3, NaNO3, NaF, Na2SiF6, etc. as raw materials.
[0068] The Al2O3 component is an arbitrary component in the second glass. When the content is greater than 0%, the chemical durability of the glass can be improved, and the viscosity of the glass when it is melted can be increased. In particular, by making the content of the Al2O3 component less than 10%, the meltability of the glass can be improved and the devitrification tendency of the glass can be reduced. Therefore, the upper limit of the content of the Al2O3 component compared to the total mass of the glass in terms of oxide conversion composition is preferably less than 10%, more preferably less than 5%, and most preferably less than 3%. The Al2O3 component can be contained in the glass using, for example, Al2O3, Al(OH)3, AlF3, etc. as raw materials.
[0069] The La2O3 component is an arbitrary component in the second glass. When the content is greater than 0%, the refractive index of the glass can be increased, and the chemical durability of the glass can be improved. In particular, by making the content of the La2O3 component less than 20%, the devitrification resistance of the glass can be improved and the Abbe number can be increased. Therefore, the upper limit of the content of the La2O3 component compared to the total mass of the glass in terms of oxide conversion composition is preferably less than 20%, more preferably less than 17%, and most preferably less than 15%. The La2O3 component can be contained in the glass using, for example, La2O3, La(NO3)3·XH2O (X is an arbitrary integer), etc. as raw materials.
[0070] The Y2O3 component is an arbitrary component in the second glass. When the content is greater than 0%, the refractive index of the glass can be increased and the Abbe number can be increased. In particular, by making the content of the Y2O3 component less than 30%, the devitrification resistance of the glass can be improved and the required optical coefficient can be obtained. Therefore, the upper limit of the content of the Y2O3 component compared to the total mass of the glass in terms of oxide conversion composition is preferably less than 30%, more preferably less than 20%, further preferably less than 17%, and most preferably less than 14%. Y2O3, for example, can be contained in the glass using Y2O3, YF3, etc. as raw materials.
[0071] The Gd2O3 component is an arbitrary component in the second glass. When the content is greater than 0%, the refractive index of the glass can be increased and the Abbe number can be increased. In particular, by making the content of the Gd2O3 component less than 20%, the devitrification resistance of the glass can be improved and the required optical coefficient can be obtained. Therefore, the upper limit of the content of the Gd2O3 component compared to the total mass of the glass in terms of oxide conversion composition is preferably less than 20%, more preferably less than 17%, and most preferably less than 14%. The Gd2O3 component can be contained in the glass using, for example, Gd2O3, GdF3, etc. as raw materials.
[0072] The Yb2O3 component is an arbitrary component in the second glass. When the content is greater than 0%, the resistance to devitrification can be improved while maintaining a high refractive index and a high Abbe number. By making the content of Yb2O3 less than 10%, the devitrification caused by excessive Yb2O3 can be reduced, and the material cost and specific gravity of the glass can be reduced. In addition, the increase in the glass transition point and the yield point can be suppressed. Therefore, the upper limit of the content of Yb2O3 is preferably less than 10%, more preferably less than 5%, still more preferably less than 2.5%, and more preferably less than 1%. The Yb2O3 component can use Yb2O3, YbF3, etc. as raw materials.
[0073] The ZrO2 component is an arbitrary component in the second glass. When its content is greater than 0%, the coloring of the glass can be reduced and the transmittance to short-wavelength visible light can be increased. It can also promote stable glass formation and improve the resistance to devitrification of the glass. On the other hand, by making the content of the ZrO2 component less than 10%, the devitrification caused by excessive inclusion of the ZrO2 component can be reduced. Therefore, the upper limit of the content of the ZrO2 component compared to the total mass of the glass in terms of oxide conversion composition is preferably less than 10%, more preferably less than 8%, and most preferably less than 7%. The ZrO2 component can be contained in the glass using, for example, ZrO2, ZrF4, etc. as raw materials.
[0074] WO3 is an arbitrary component in the second glass. When the content is greater than 0%, the refractive index of the glass can be increased and the Abbe number can be increased. In particular, by making the content of WO3 less than 10%, the devitrification resistance of the glass can be improved, and the transmittance of the glass to short-wavelength visible light can be suppressed. Therefore, the upper limit of the content of WO3 relative to the total mass of the glass in terms of oxide conversion composition is preferably 10% or less, more preferably 7% or less, and most preferably 5% or less.
[0075] Ta2O5 is an arbitrary component in the second glass. When the content is greater than 0%, the refractive index of the glass can be increased, and the resistance to devitrification of the glass can be improved. On the other hand, by making the content of Ta2O5 less than 10%, the amount of Ta2O5 used as a rare mineral resource can be reduced, and the glass is easily melted at a lower temperature, so the production cost of the glass can be reduced. In addition, thereby, the devitrification of the glass caused by excessive inclusion of Ta2O5 can be reduced. Therefore, the content of Ta2O5 is preferably less than 10%, more preferably less than 7%, and more preferably less than 5%. Ta2O5 can use Ta2O5 and the like as a raw material.
[0076] The ZnO component is an arbitrary component in the second glass. When the content is greater than 0%, the liquidus temperature of the glass can be lowered and the devitrification resistance of the glass can be improved. In particular, by making the content of the ZnO component less than 20%, a high refractive index and a low dispersion can be easily obtained. Therefore, the upper limit of the content of the ZnO component compared to the total mass of the glass in terms of oxide conversion composition is preferably less than 20%, more preferably less than 10%, and most preferably less than 5%. The ZnO component can be contained in the glass using, for example, ZnO, ZnF2, etc. as raw materials.
[0077] MgO is an arbitrary component in the second glass. When the content is greater than 0%, the liquidus temperature of the glass can be lowered, the devitrification resistance of the glass can be improved, and the transmittance to visible light is difficult to be reduced. In particular, by making the content of the MgO component less than 10%, a high refractive index and low dispersion can be easily obtained. Therefore, the upper limit of the content of the MgO component relative to the total mass of the glass in terms of oxide conversion composition is preferably less than 10%, more preferably less than 5%, and most preferably less than 3%. The MgO component can be contained in the glass using, for example, MgCO3, MgF2, etc. as raw materials.
[0078] The CaO component is an arbitrary component in the second glass. When the content is greater than 0%, the liquidus temperature of the glass can be lowered, and the resistance to devitrification of the glass can be improved. In particular, by making the content of the CaO component less than 12%, a high refractive index and low dispersion can be easily obtained, and the resistance to devitrification of the glass and the reduction of chemical durability can be suppressed. Therefore, the upper limit of the content of the CaO component compared to the total mass of the glass in terms of oxide conversion composition is preferably less than 12%, more preferably less than 10%, and most preferably less than 8%. The CaO component can be contained in the glass using, for example, CaCO3, CaF2, etc. as raw materials.
[0079] The SrO component is an arbitrary component in the second glass. When the content is greater than 0%, the liquidus temperature of the glass can be lowered and the resistance to devitrification of the glass can be improved. In particular, by making the content of the SrO component less than 10%, a high refractive index and low dispersion can be easily obtained, and the reduction in the resistance to devitrification and chemical durability of the glass can be suppressed. Therefore, the upper limit of the content of the SrO component compared to the total mass of the glass in terms of oxide conversion composition is preferably less than 10%, more preferably less than 5%, and most preferably less than 3%. The SrO component can be contained in the glass using, for example, Sr(NO3)2, SrF2, etc. as raw materials.
[0080] The Li2O component is an arbitrary component in the second glass, and when the content is greater than 0%, the melting temperature of the glass can be lowered. In particular, by making the content of the Li2O component less than 10%, a high refractive index can be easily obtained, and the stability of the glass can be improved and the occurrence of devitrification can be reduced. Therefore, the upper limit of the content of the Li2O component compared to the total mass of the glass in terms of oxide conversion composition is preferably less than 10%, more preferably less than 5%, and most preferably less than 3%. The Li2O component can be contained in the glass using, for example, Li2CO3, LiNO3, LiF, etc. as raw materials.
[0081] The K2O component is an arbitrary component in the second glass, and when the content is greater than 0%, the melting temperature of the glass can be lowered. In particular, by making the content of the K2O component less than 10%, a high refractive index can be easily obtained, and the stability of the glass can be improved and the occurrence of devitrification can be reduced. Therefore, the upper limit of the content of the K2O component compared to the total mass of the glass in terms of oxide conversion composition is preferably less than 10%, more preferably less than 7%, and further preferably less than 5%. The K2O component can be contained in the glass using, for example, K2CO3, KNO3, KF, KHF2, K2SiF6, etc. as raw materials.
[0082] Sb2O3 component is an arbitrary component in the second glass, which can improve the transmittance of glass to short-wavelength visible light and has a defoaming effect when melting glass. Therefore, by making the content of Sb2O3 component less than 0.1%, the coloring of high-refractive index glass can be particularly suppressed. In addition, by being less than 0.1%, it is difficult to produce excessive foaming when the glass is melted, so Sb2O3 component is difficult to alloy with melting equipment (especially precious metals such as Pt). Therefore, the content of Sb2O3 component compared to the total mass of glass composed of oxide conversion has an upper limit of less than 0.1%, preferably less than 0.05%.
[0083] SnO2 is an arbitrary component in the second glass, and when the content is greater than 0%, it has the effect of clarifying the molten glass as a defoaming agent. In particular, by containing the SnO2 component, the above effect can be obtained, and the devitrification of the glass is less likely to occur. Therefore, the upper limit of the content of the SnO2 component compared to the total mass of the glass in terms of oxide conversion composition is preferably 2% or less, and more preferably 1% or less. The SnO2 component can be contained in the glass using SnO, SnO2, SnF2, SnF4, etc. as raw materials.
[0084] <About ingredients that should not be contained>
[0085] Next, components that should not be contained in the optical glass of the present invention and components that are preferably not contained are described.
[0086] Other components can be added as needed within the range that does not impair the characteristics of the glass of the present invention. However, in addition to Ti, Zr, Nb, W, La, Gd, Y, Yb, and Lu, various transition metal components such as Nd, V, Cr, Mn, Fe, Co, Ni, Cu, Ag, and Mo have the property of causing glass coloration even in a small amount when contained alone or in a composite form, and absorbing light of a specific wavelength in the visible light region, and therefore, in particular, in optical glasses using wavelengths in the visible light region, it is preferably not substantially contained.
[0087] In addition, lead compounds such as PbO and arsenic compounds such as As2O3 are components with high environmental burdens, and therefore, it is preferred that they are substantially not contained, that is, they are not contained at all except for unavoidable contamination.
[0088] In addition, Th, Cd, Tl, Os, Be and Se are each considered harmful chemical substances and are therefore avoided in recent years. Environmental measures must be taken not only in the glass manufacturing process but also in the processing process and until the waste treatment after the glass is manufactured. Therefore, when the environmental impact is important, it is preferred that these components are not substantially contained.
[0089] <About reducing agents>
[0090] The optical glass of the present invention is characterized in that a reducing agent is added as part of the glass raw material. By adding the reducing agent, platinum can be suppressed from mixing into the glass, and the transmittance can be improved. The upper limit of the content of the reducing agent compared to the total mass of the glass in terms of oxide conversion composition is preferably 5% or less, more preferably 3% or less, further preferably 2% or less, and most preferably 1% or less. As the reducing agent, for example, single substances such as carbon and S, organic compounds, or raw materials such as ammonium sulfate that generate reducing gas when thermally decomposed can be listed.
[0091] Specific examples include: sucrose, silicon acetate, lithium acetate, sodium acetate, potassium acetate, calcium acetate, strontium acetate, barium acetate, lanthanum acetate, lithium oxalate, sodium oxalate, potassium oxalate, calcium oxalate, strontium oxalate, barium oxalate, lanthanum oxalate, silicon sulfide, lithium sulfide, sodium sulfide, potassium sulfide, calcium sulfide, strontium sulfide, barium sulfide, zinc sulfide, tungsten sulfide, titanium sulfide, lanthanum sulfide, antimony sulfide and other raw materials.
[0092] It should be noted that the reducing agent may be any material that has a reducing agent effect when melted, and is not limited to the above-mentioned materials.
[0093] <About Defoaming Agent>
[0094] The optical glass of the present invention is characterized in that a defoamer is added as part of the glass raw material. By adding the defoamer together with the reducing agent, a glass with further improved defoaming properties can be obtained compared with adding only the defoamer. The upper limit of the content of the defoamer relative to the total mass of the glass in terms of oxide conversion composition is preferably 3% or less, more preferably 2% or less, and most preferably 1% or less. Examples of the defoamer include sulfates such as SO2 and Na2SO4, and Sb2O3 components.
[0095] The optical glass of the present invention is characterized in that water is not supplied in the melting step. In the present invention, water is not supplied, which means that water vapor is not added to the melting atmosphere or bubbling is not performed, that is, no special step is performed. Other methods of not supplying water include adding dry gas in the melting step, performing the melting step in an inert atmosphere, etc.
[0096] [Manufacturing method]
[0097] The optical glass of the present invention can be produced, for example, as follows. That is, the above raw materials are uniformly mixed so that each component is within a predetermined content range, and the prepared mixture is placed in a platinum crucible, and depending on the melting difficulty of the glass raw materials, an electric furnace is used to melt them at a temperature range of 1100° C. to 1500° C. for 2 to 5 hours, and after stirring to homogenize them, the temperature is lowered to an appropriate level, and then cast in a casting mold and slowly cooled to produce the optical glass of the present invention.
[0098] [physical properties]
[0099] The optical glass of the present invention preferably has a high refractive index and high dispersion (low Abbe number).
[0100] The refractive index of the first glass (n d ) is preferably 1.75 or more, more preferably 1.80 or more, and even more preferably 1.85 or more. d ) is preferably 2.10 or less, more preferably 2.07 or less, and even more preferably 2.05 or less. d ) is preferably 20 or more, more preferably 23 or more, and still more preferably 25 or more. d ) is preferably 45 or less, more preferably 40 or less, and still more preferably 37 or less.
[0101] The refractive index of the second glass (n d ) is preferably 1.50 or more, more preferably 1.52 or more, and even more preferably 1.53 or more. d ) is preferably 2.10 or less, more preferably 2.07 or less, and even more preferably 2.05 or less. d ) is preferably 15 or more, more preferably 17 or more, and even more preferably 19 or more. The Abbe number (ν d ) is preferably 53 or less, more preferably 51 or less, and still more preferably 50 or less.
[0102] By having such a high refractive index, it is possible to achieve a larger amount of light refraction while realizing a thinner optical element. In addition, by having such a low dispersion, when used as a single lens, the focus shift (chromatic aberration) caused by the wavelength of light can be reduced. Therefore, for example, when an optical system is formed by combining with an optical element having a high dispersion (low Abbe number), the aberration of the entire optical system can be reduced, and high imaging characteristics can be achieved.
[0103] Thus, the optical glass of the present invention can play an effective role in optical design. In particular, when constituting an optical system, in addition to achieving high imaging characteristics, it can also achieve miniaturization of the optical system and increase the degree of freedom in optical design.
[0104] The optical glass of the present invention preferably has a high visible light transmittance, particularly a high transmittance of light on the short wavelength side of visible light, and has little coloration.
[0105] The shortest wavelength (λ) of the first glass sample with a thickness of 10 mm when the spectral transmittance is 70% 70 ), the upper limit of which is preferably 470 nm or less, more preferably 450 nm or less, and even more preferably 430 nm or less. In addition, the shortest wavelength (λ5) when the sample of the optical glass of the first glass of the present invention having a thickness of 10 mm shows a spectral transmittance of 5%, the upper limit of which is preferably 390 nm or less, more preferably 380 nm or less, and even more preferably 370 nm or less.
[0106] The sample with a thickness of 10 mm of the second glass shows the shortest wavelength (λ 70 ), the upper limit of which is preferably 500 nm or less, more preferably 490 nm or less, and even more preferably 480 nm or less. In addition, the shortest wavelength (λ5) when the sample of the optical glass of the second glass of the present invention having a thickness of 10 mm shows a spectral transmittance of 5%, the upper limit of which is preferably 390 nm or less, more preferably 385 nm or less, and even more preferably 370 nm or less.
[0107] Therefore, since the absorption edge of the glass is located in the ultraviolet region or in the vicinity thereof and the glass has high transparency to visible light, the optical glass can be preferably used as an optical element that transmits light, such as a lens.
[0108] The optical glass of the present invention preferably has a low platinum content and thus has little coloration.
[0109] In particular, the platinum content in the optical glass of the present invention is preferably 10 ppm or less, more preferably 9 ppm or less, and even more preferably 8 ppm or less. This can suppress coloring caused by platinum and improve the transparency of the glass to visible light, so the optical glass can be preferably used as an optical element that allows light to pass, such as a lens.
[0110] [Preform and optical element]
[0111] A glass molded body can be produced from the produced optical glass by a grinding method, or a press molding method such as reheating press molding, precision press molding, etc. That is, the glass molded body can be produced by the following methods: the optical glass is subjected to mechanical processing such as grinding and polishing to produce the glass molded body; or a preform for press molding is produced from the optical glass, and the preform is subjected to reheating press molding, and then subjected to grinding to produce the glass molded body; or a preform produced by grinding, or a preform formed by known float molding, etc., is subjected to precision press molding to produce the glass molded body. In addition, the method of producing the glass molded body is not limited to the above methods.
[0112] Thus, the optical glass of the present invention can be used in a variety of optical elements and optical designs. In particular, a preform is formed from the optical glass of the present invention, and the preform is used to perform reheating press forming or precision press forming to produce an optical element such as a lens or a prism. Thus, a preform with a larger diameter can be formed, so that the optical element can be enlarged, and when used in optical equipment such as a camera or a projector, high-definition and high-precision imaging characteristics and projection characteristics can be achieved.
[0113] Example
[0114] Compositions of the first glass of the present invention and comparative examples, and the refractive indexes (n d ), Abbe number (ν d ), the wavelength (λ) when the spectral transmittance is 70% and 5% 70 The results of the measurement of the platinum content (ppm) in the glass, and the measured values of bubbles (gas bubbles) in the glass are shown in Table 1; the compositions of the second glass examples, and the refractive index (n d ), Abbe number (ν d ), the wavelength (λ) when the spectral transmittance is 70% and 5% 70, λ5), the results of the platinum content (ppm) in the glass, and the measured values of bubbles (gas bubbles) in the glass are shown in Table 2. It should be noted that the reducing agent (carbon) described in the embodiments of the first glass and the second glass is not limited to raw materials of carbon (C) alone, and includes, for example, raw materials in which the amount of C (carbon) that does not become CO2 due to insufficient oxygen when carbon contained in a hypothetical raw material such as acetate, oxalate, etc. combines with oxygen to form CO2. Similarly, the reducing agent (sulfur) is not limited to raw materials of S (sulfur) alone, and includes, for example, examples of raw materials in which the amount of S (sulfur) that does not become SO2 due to insufficient oxygen when sulfur contained in a hypothetical sulfide raw material combines with oxygen to form SO2. In addition, in the composition of the embodiments of the first glass and the second glass, when Sb2O3 is contained, it includes acting as a defoaming agent. The purpose of the following embodiments is merely illustrative and is not limited to these embodiments.
[0115] The glass of the embodiments of the present invention uses high-purity raw materials such as oxides, hydroxides, carbonates, nitrates, fluorides, and metaphosphate compounds corresponding to the raw materials as raw materials for optical glasses as raw materials of various components. These raw materials are weighed and uniformly mixed in the proportions of the compositions of the embodiments shown in the table, and then put into a platinum crucible. Depending on the melting difficulty of the glass raw materials, they are melted in an electric furnace at a temperature range of 1100 to 1500° C. for 2 to 5 hours, stirred to homogenize the raw materials, and then cast in a mold and slowly cooled to produce glass.
[0116] The refractive index (n d ), in accordance with the V block method specified in JIS B 7071-2:2018, expressed as a measured value for the d line (587.56nm) of a helium lamp. In addition, the refractive index of the d line and the refractive index of the F line (486.13nm) of a hydrogen lamp are used. F ), the refractive index (n C ) value, according to the Abbe number (ν d )=[(n d -1) / (n F -n C )] to calculate the Abbe number (ν d Then, according to the obtained refractive index (n d ) and Abbe number (ν d ) value, find the relationship n d =-a×ν d +b is the intercept b when the slope a is 0.01.
[0117] The transmittance of the glass of the embodiment and comparative example is measured according to the standard of the Japanese Optical Glass Industry Association JOGIS02. It should be noted that in the present invention, the presence and degree of coloration of the glass can be obtained by measuring the transmittance of the glass. Specifically, the relative surfaces of the glass block material are parallel ground to a sample with a thickness of 10±0.1mm, and after annealing, the light transmittance (spectral transmittance), λ 70 (wavelength when the transmittance is 70%), λ5 (wavelength when the transmittance is 5%).
[0118] The platinum content (ppm) in the glasses of Examples and Comparative Examples was measured using ICP-MS (inductively coupled plasma mass spectrometry).
[0119] The bubbles in the glasses of Examples and Comparative Examples were measured based on Japan Optical Glass Industry Association Standard JOGIS12-2012 “Method for measuring bubbles in optical glass”.
[0120]
Table 1
[0121]
[0122]
Table 2
[0123]
[0124] ※When Sb2O3 is contained, it also acts as a defoaming agent
[0125] As shown in the table, the first glass of the embodiment of the present invention has a refractive index (n d ) are all greater than 1.75, and more specifically, are all greater than 1.90, and the refractive index (n d ) are all below 2.10, and in more detail, are all below 2.05, which are within the required range.
[0126] In addition, the second glass of the embodiment of the present invention has a refractive index (n d ) are all greater than 1.75, and more specifically, are all greater than 1.80, which are within the required range.
[0127] The first glass of the embodiment of the present invention has an Abbe number (ν d ) are all greater than 25, more specifically, are all greater than 26, and their Abbe numbers (ν d ) are all below 45, and more specifically, are all below 40, which is within the required range.
[0128] In addition, the second glass of the embodiment of the present invention has an Abbe number (ν d ) are all greater than 15, and in more detail, are all greater than 23, which are within the required range.
[0129] The first glass of the embodiment of the present invention, λ 70 (wavelength at which the transmittance is 70%) is 450 nm or less. 70 It is larger than 450 nm. Therefore, it is understood that the optical glass of the example of the present invention is more difficult to be colored than the glass of the comparative example.
[0130] The optical glasses of the examples of the present invention all have a platinum content of 9 ppm or less. In contrast, the glass of the comparative example has a platinum content of 11.1 ppm. Therefore, it can be seen that the glass of the examples of the present invention has less platinum than the glass of the comparative example.
[0131] The optical glasses of the examples of the present invention were rated within level 3. In contrast, the glasses of the comparative examples were rated at level 5. Therefore, it can be seen that the optical glasses of the examples of the present invention have sufficiently eliminated bubbles compared to the glasses of the comparative examples, and the defoaming effect is obviously better than that of the glasses of the comparative examples.
[0132] Therefore, it is clear that the optical glass of the embodiment of the present invention contains a predetermined amount of reducing agent, so that the refractive index (n d ) and Abbe number (ν d ) is within the required range, the transmittance is increased, and it is difficult to produce coloring caused by platinum. In addition, it is clear that the optical glass of the embodiment of the present invention can improve the defoaming property by containing a specified amount of reducing agent and defoaming agent.
[0133] Although the present invention has been described in detail above for the purpose of illustration, the purpose of this embodiment is only for illustration, and it should be fully understood that those skilled in the art can make many changes to the present invention without departing from the spirit and scope of the present invention.
Claims
1. A method for manufacturing optical glass, characterized in that: include: The step of mixing the raw materials; and The mixed raw materials are placed in a platinum crucible to melt glass without supplying water, wherein: The raw material contains a reducing agent, The optical glass contains, in terms of mass %, compared to the total mass of the glass in terms of oxide conversion composition: 30% to 65% La2O3 content, 1% to 25% B2O3 content, WO3 content greater than 0% and less than 15%, Nb2O5 content below 15%, SiO2 content below 15%, 6% or more and 25% or less of TiO2, and 15% or less Y2O3 content, and The platinum content is 8.8 ppm or less and substantially no PbO component and Sb2O3 component are contained, and, Refractive index (n d ) is 1.90 or more and 2.10 or less and the Abbe number (ν d ) is 20 or more and 37 or less, The sample with a thickness of 10 mm shows the shortest wavelength (λ) when the spectral transmittance is 70%. 70 ) is 421 nm or less and the shortest wavelength (λ5) when showing a spectral transmittance of 5% is 368.5 nm or less.
2. A method for manufacturing optical glass, characterized in that: include: The step of mixing the raw materials; and The mixed raw materials are placed in a platinum crucible to melt glass without supplying water, wherein: The raw material contains a reducing agent, The optical glass contains, in terms of mass %, compared to the total mass of the glass in terms of oxide conversion composition: 5% to 75% SiO2 content, 5% to 40% TiO2 content, and 3.05% or less La2O3 content, and It does not contain Gd2O3, Y2O3, Sb2O3 and PbO components. Refractive index (n d ) is 1.80 or more and 2.10 or less and the Abbe number (ν d ) is greater than 15 and less than 25.43, The sample with a thickness of 10 mm shows the shortest wavelength (λ) when the spectral transmittance is 70%. 70 ) is 408 nm or less and the shortest wavelength (λ5) when showing a spectral transmittance of 5% is 369 nm or less.
3. A method for manufacturing optical glass, characterized in that: include: The step of mixing the raw materials; and The mixed raw materials are placed in a platinum crucible to melt glass without supplying water, wherein: The raw materials contain reducing agents and defoaming agents, The optical glass contains, in terms of mass %, compared to the total mass of the glass in terms of oxide conversion composition: 30% to 65% La2O3 content, 1% to 25% B2O3 content, WO3 content greater than 0% and less than 15%, Nb2O5 content below 15%, SiO2 content below 15%, 6% or more and 25% or less of TiO2, and 15% or less Y2O3 content, and The platinum content is 8.8 ppm or less and substantially no PbO component and Sb2O3 component are contained, and, Refractive index (n d ) is 1.90 or more and 2.10 or less and the Abbe number (ν d ) is 20 or more and 37 or less, The sample with a thickness of 10 mm shows the shortest wavelength (λ) when the spectral transmittance is 70%. 70 ) is 421 nm or less and the shortest wavelength (λ5) when showing a spectral transmittance of 5% is 368.5 nm or less.
4. A method for manufacturing optical glass, characterized in that: include: The step of mixing the raw materials; and The mixed raw materials are placed in a platinum crucible to melt glass without supplying water, wherein: The raw materials contain reducing agents and defoaming agents, The optical glass contains, in terms of mass %, compared to the total mass of the glass in terms of oxide conversion composition: 5% to 75% SiO2 content, 5% to 40% TiO2 content, and 3.05% or less La2O3 content, and It does not contain Gd2O3, Y2O3, Sb2O3 and PbO components. Refractive index (n d ) is 1.80 or more and 2.10 or less and the Abbe number (ν d ) is greater than 15 and less than 25.43, The sample with a thickness of 10 mm shows the shortest wavelength (λ) when the spectral transmittance is 70%. 70 ) is 408 nm or less and the shortest wavelength (λ5) when showing a spectral transmittance of 5% is 369 nm or less.
5. The method for producing an optical glass according to any one of claims 1 to 4, wherein: The raw materials contain nitrate or carbonate.
Citation Information
Patent Citations
Optical glass and optical element
JP2019019050A